GENETICS OF BROWN PLANTHOPPER (NILAPARVATA LUGENS STAL.) RESISTANCE IN ELITE DONORS OF RICE (ORYZA SATIVA L.) - B. BALAKRISHNA; P. V. SATYANARAYANA (The Bioscan, 2013)
The inheritance of resistance to the brown planthopper (BPH) in four BPH resistant donors of rice i. e., Sinna Sivappu, Sudu Hondarawala, PTB 33 and BM 71 was studied both in field and greenhouse conditions. The F2 population of crosses involving donors Sinna Sivappu, Sudu Hondarawala and PTB 33 fit into the ratio of 13:3 indicating the resistance to BPH was controlled by two genes i. e., one dominant and one recessive gene segregating independent to each other. The F2 population of donor BM 71 involving crosses fit into the ratio of 3:1 revealing single dominant gene control of BPH resistance. So that BM 71 can be used for easy incorporation of BPH resistance into susceptible high yielding rice varieties.